From polygyny to serial monogamy: A unified theory of marriage institutions - David De la Croix; Fabio Mariani (Institute for the Study of Labor (IZA), 2012)
Consider an economy populated by males and females, both rich and poor. The society has to choose one of the following marriage institutions: polygyny, strict monogamy, and serial monogamy (divorce and remarriage). After having identified the conditions under which each of these equilibria exists, we show that a rise in the share of rich males can explain a change of regime from polygyny to monogamy. The introduction of serial monogamy follows from a further rise in either the proportion of rich males, or an increase in the proportion of rich females. Strict monogamy is a prerequisite to serial monogamy, as it promotes the upward social mobility of females more than polygyny. We also show that polygyny is compatible with democracy.
urn:nbn:de:101:1-201305294571
Keywords: J12; O17; Z13; 330; marriage; polygyny; monogamy; divorce; human capital; political economy; Ehe; Institutionalismus; Scheidung; Einkommensverteilung; Soziale Mobilität; Public Choice; Theorie